EurASEAA14 : papers from the fourteenth International Conference of the European Association of Southeast Asian Archaeologists. - Lewis, Helen (Archaeologist), (Access archaeology., 2020)
This volume comprises papers originally presented at the EurASEAA14 conference in 2012, updated for publication. It focuses on topics under the broad themes of archaeology and art history, epigraphy, philology, historic archaeology, ethnography, ethnoarchaeology, ethnomusicology, materials studies, and long-distance trade and exchange.